Real world applications of fractional models by Atangana-Baleanu fractional derivative - Bas, Erdal; Ozarslan, Ramazan (Pergamon-Elsevier Science Ltd, 2018)
In this study, some modeling problems, Newton,'s law of cooling, population growth, logistic equation, blood alcohol model, are considered by Atangana-Baleanu fractional derivative. Analytical solutions are obtained by Laplace transform and results are simulated by figures under different orders. Atangana-Baleanu fractional derivative gives more precise results to the derivative with exponential kernel because of having fractional order, and so it is a generalized version of the derivative with exponential kernel. (C) 2018 Elsevier Ltd. All rights reserved.
Keywords: Fractional operator; Atangana-Baleanu fractional derivative; Mittag-Leffler kernel; Laplace transform; Modeling problems